Must US Medical Professionals Treat Ebola Patients? - Robert Nowell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
In this paper I examine the duty of US healthcare providers (HCPs) to treat patients in the context of the current Ebola virus disease (EVD) outbreak. In particular, I consider how EVD and subsequent treatment is different from other infectious diseases like influenza or SARS, and how this impacts duty of care for US HCPs. I conclude that, given proper protective measures and support, HCPs at present face a strong moral obligation to care for patients with EVD. This duty is dependent upon individual position and context, and it may change if, for example, the situation turns into a pandemic.